Sesapan: Wacana Pelestarian Lingkungan, Mohon Keselamatan, dan Menjinakkan Binatang Piaraan dalam Teks Sastra Lisan di Bali - Puspawati, Luh Putu; Suardiana, I Wayan; Suastika, I Made (Humanis, 2023)
This research is aimed at examining the potential of Balinese oral literature in strengthening traditional values ??in the context of national development, especially in for Human Resources. The data collection method was carried out by tracking oral texts in several lontar texts and printed texts in the form of books in libraries. Qualitative data about sesapan is 'dissected' using hermeneutic theory. Data were analyzed using descriptive analytical methods assisted by inductive techniques. Data presentation is carried out using informal methods using description techniques. The research shows that the text of Sesapan has religious value for preserving the environment, asking for safety, and taming domestic animals. Maintaining a good environment will ensure the life of creatures on earth. People use sesapan texts when they use things in nature, such as when cutting down trees, carrying out activities in certain places that are considered haunted, when an earthquake occurs, and so on.